Cardiac Safety of Omadacycline in the IV/oral Phase 3 Acute Bacterial Skin and Skin Structure Infection (ABSSSI) and in the IV/oral Phase 3 Community-acquired Bacterial Pneumonia (CABP) Studies. (4th October 2017) - Darpo, Borje; Tzanis, Evan; Garrity-Ryan, Lynne; Manley, Amy; McGovern, Paul; Loh, Evan
Abstract: Background: Omadacycline (OMC) is a novel aminomethylcycline antibiotic. In Phase 1 studies asymptomatic increases in heart rate (HR) were observed following OMC dosing in healthy volunteers. In vitro studies showed OMC inhibits binding of acetylcholine to the M2 -subtype of the muscarinic receptor, resulting in a nonadrenergic, vagolytic effect. In a thorough QT study, OMC had no clinically meaningful effect on the QTc interval or any other ECG parameters. Phase 3 studies of OMC as an oral (PO) and intravenous (IV) monotherapy for ABSSSI and CABP were recently completed. Methods: In the ABSSSI and CABP studies OMC was dosed 100 mg IV q12h × 2 doses then 100 mg IV q24h. After ≥ 3 days IV therapy subjects could switch to 300 mg PO q24h for a total treatment duration of 7–14 days. The comparator for ABSSSI was linezolid (LZD) 600 mg IV/PO q12h and for CABP moxifloxacin (MOX) 400 mg IV/PO q24h. HR and blood pressure (BP) were measured at screening, before and after the first 3 doses and at all visits through Post Therapy Evaluation. A 12-lead ECG was performed at screening, before and after doses 1 and 3, on Day 7 and at the end of treatment. Adverse events (AEs) were monitored through a Final Follow-up visit 30–37 days after first dose. Results: The safety populations included 323 OMC and 322 LZD subjects in ABSSSI and 382 OMC and 388 MOX subjects in CABP. In the ABSSSI study the incidence of cardiac treatment-emergent AEs (TEAEs) was 4 (1.2%) and 3 (0.9%) and of tachycardia TEAEs specifically was 1 (0.3%) and 0 in OMC and LZD subjects, respectively. In the CABP study the incidence of cardiac TEAEs was 15 (3.9%) and 20 (5.2%) and tachycardia was 4 (1.0%) and 3 (0.8%) in OMC and MOX subjects, respectively. In both studies HR tended to decline over time in OMC and comparator groups. At any given post-Baseline time point, the mean HR in OMC subjects was slightly higher than comparator subjects (difference of < 6 bpm from LZD in ABSSSI, < 3 bpm from MOX in CABP), with no clinically significant difference in outlying values. No clinically meaningful changes in BP or ECG parameters were noted in either study. Conclusion: OMC inhibition of acetylcholine binding to the M2 -subtype of the muscarinic receptor was not associated with clinically meaningful effects on HR, BP, ECG or cardiac safety in ABSSSI or CABP subjects. Disclosures: B. Darpo, iCardiac Technologies: Shareholder, Stock Options; E. Tzanis, Paratek Pharmaceuticals: Employee and Shareholder, Salary; L. Garrity-Ryan, Paratek Pharmaceuticals: Employee and Shareholder, Salary; A. Manley, Paratek Pharmaceuticals: Employee and Shareholder, Salary; P. McGovern, Paratek Pharmaceuticals: Employee and Shareholder, Salary; E. Loh, Paratek Pharmaceuticals: Board Member, Employee and Shareholder, Salary